Pengaruh Kompensasi Finansial Dan Lingkungan Kerja Terhadap Organizational Citizenship Behavior (OCB) Karyawan Bagian Produksi Pada PT Sinar Jaya Inti Mulya Kota Metro - Suhada, Bambang; Japlani, Ardiansyah; Kurniadi, Panji (Universitas Muhammadiyah Metro, 2023)
The purpose of research to determine the influence of financial compensation and workenvironment on organizational citizenship behavior (OCB) of production division employeesat PT Sinar Jaya Inti Mulya, Metro, Lampung. The type of research that used is descriptiveresearch with a quantitative approach with the object of research is financial compensation,work environment and organizational citizenship behavior (OCB). The population of thisresearch is all employees of the Production Department at PT Sinar Jaya Inti Mulya MetroLampung City with a total sample of 65 respondents The technique of collecting data usingquestionnaires and literature study. Analyzer uses multiple linear regression analysis. Theresults showed that partially or simultaneously there is a positive and significant effect offinancial compensation and work environment on the Organizational Citizenship Behavior(OCB) of Production Section Employees at PT Sinar Jaya Inti Mulya, Metro City, Lampung.